Iso Isolasi Bakteri Selulolitik Asal Saluran Pencernaan Rayap Dan Daya Hidupnya Pada Berbagai Substrak Yang Berasal Dari Limbah Pertanian Dan Perkebunan - Susanti, Vivi; Mairizal, Mairizal; Yurleni, Yurleni; Adriani, Adriani; Manin, Fahmida (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2021)
ABSTRACT This study aimed to identify isolates that produce cellulase enzymes derived from cellulolytic bacteria from the digestive tract of termites and to determine the best type of substrate as the carrier and survival of these isolates. This research consists of 3 (three) stages. The first stage of research was the isolation of cellulolytic bacteria using descriptive data analysis. The second stage of research was to determine the best carrier for selected cellulolytic isolates, while the third stage was to determine the shelf life of the isolates with the selected substrate as the best carrier by analyzing data using analysis of variance. The results of the first phase of research obtained 3 isolates of cellulolytic bacteria from the best termite digestive tract based on the clear zone index test with isolate code VR52, VR61 and VR81 with clear zone index for each isolate 1.087; 2,250 and 1,710 mm. Based on Gram staining, the three isolates were gram-positive bacteria in the form of bacilli. Maximum enzyme activity in isolate VR61 (Bacillus sp) with its enzyme activity (19.91 Âµ/mL). The results of the second stage study showed that rice bran was the best sAubstrate based on total microbes with a value of 202 x 109 CFU / g. The results of the third stage research showed that the number of cellulolytic bacteria in the selected sub-extract (rice bran) at a storage temperature of 4oC (178.92 x 109 CFU / gr) was more than that of storage at 27oC (101.69 x 109 CFU / gr). This research concludes that the longer the storage time shows a decrease in the number of bacteria and pH in the sub-extract. The best interaction on rice bran sub-extract as a carrier at a storage temperature of 4oC in the second week with the number of cellulolytic bacteria 197.8 x 109 CFU / gr with a pH value of 6.46 and the fourth week of 167.85 x 109 CFU / gr with a pH value of 6.39. Â  Keywords: Cellulose, Cellulolytic Bacteria, Termites